2017
DOI: 10.1002/2017ms000960
|View full text |Cite
|
Sign up to set email alerts
|

Coupled mesoscale‐LES modeling of a diurnal cycle during the CWEX‐13 field campaign: From weather to boundary‐layer eddies

Abstract: Multiscale modeling of a diurnal cycle of real‐world conditions is presented for the first time, validated using data from the CWEX‐13 field experiment. Dynamical downscaling from synoptic‐scale down to resolved three‐dimensional eddies in the atmospheric boundary layer (ABL) was performed, spanning 4 orders of magnitude in horizontal grid resolution: from 111 km down to 8.2 m (30 m) in stable (convective) conditions. Computationally efficient mesoscale‐to‐microscale transition was made possible by the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 67 publications
(85 reference statements)
3
93
0
Order By: Relevance
“…No major synoptic events affected the area during this period. Moreover, when the nearsurface flows are southerly, the WC and the surface flux station measure winds unaffected by wind turbines (Muñoz-Esparza et al, 2017). Additionally, no curtailment of wind turbines occurred and the instruments operated normally during the period, making these 4 days ideal for model verification.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…No major synoptic events affected the area during this period. Moreover, when the nearsurface flows are southerly, the WC and the surface flux station measure winds unaffected by wind turbines (Muñoz-Esparza et al, 2017). Additionally, no curtailment of wind turbines occurred and the instruments operated normally during the period, making these 4 days ideal for model verification.…”
Section: Observationsmentioning
confidence: 99%
“…This campaign was a component of the larger CWEX project, which explored the interactions of wind turbines with crops, surface fluxes, and near-surface flows in different atmospheric stability regimes in flat terrain (Rajewski et al, 2013). Research facilitated by the CWEX projects include diurnal changes in observed turbine wakes (Rhodes and Lundquist, 2013), turbine interactions with moisture and carbon dioxide fluxes , LES modelling of turbine wakes in changing stability regimes , nocturnal low-level jet (LLJ) occurrences (Vanderwende et al, 2015), diurnal changes of the microclimate near wind turbines (Rajewski et al, 2016), multiple-wake interactions (Bodini et al, 2017), the evolution of turbine wakes during the evening transition (Lee and Lundquist, 2017), and coupled mesoscalemicroscale modelling (Muñoz-Esparza et al, 2017).…”
Section: Observationsmentioning
confidence: 99%
“…This result suggests that the GZ domain 10 is lacking energy for the three simulations, and that a better treatment of turbulence at this scale is needed as will be further discussed in Section 4.3. At the micro scale domain, the spectra are substantially more energetic at higher frequencies and exhibit the f −1 decay seen in Muñoz-Esparza et al (2017) for these frequencies, also exclusively in the nested LES domain.…”
Section: Sh_les Exhibit Higher Psd Values When Compared To Les_les Bementioning
confidence: 90%
“…Under the first coupling approach, the GZ is avoided but turbulence generation methods must still be applied to the meso scale fields before they can be used as driving inflow to LES (Haupt et al, 2015;Mirocha et al, 2013). Under the second coupling approach, an adequate treatment of GZ resolutions is required and may be achieved by developing more flexible parameterizations (Shin and Dudhia, 2016;Ito et al, 2015) or by avoiding the GZ domains altogether and relying on turbulence generation strategies alone to couple meso and micro scale domains (Muñoz-Esparza et al, 2017).…”
Section: Durationmentioning
confidence: 99%
See 1 more Smart Citation